Validation of the Icare® TONOVET plus rebound tonometer in normal rabbit eyes. (August 2019) - Gloe, Shawna; Rothering, Abby; Kiland, Julie A.; McLellan, Gillian J.
Abstract: To determine the accuracy and precision of the Icare ® TONOVET Plus rebound tonometer for measuring intraocular pressure (IOP) in normal rabbit eyes, as well as compare it to three other commercially available tonometers: the Icare ® TONOVET (TV01), Tono-Pen Vet™, and Tono-Pen AVIA Vet™. The anterior chambers of both eyes of three New Zealand White rabbits were cannulated, post-mortem. IOP was measured using each of the above four tonometers at manometric pressures ranging between 5 mmHg and 70 mmHg. Data were analyzed by linear regression, ANOVA, and Bland-Altman plots. A p-value of ≤0.05 was considered significant for all statistical tests. IOP values obtained with the TONOVET Plus (in 'lapine' mode) were significantly closer to manometric IOP than those obtained with the other tonometers tested. The TV01 (in 'd' dog setting) and Tono-Pen AVIA Vet™ were significantly more accurate compared to the Tono-Pen Vet™. All tonometers had high levels of precision, though the TONOVET Plus and TV01 were significantly more precise compared to the Tono-Pen AVIA Vet™. All tonometers tended to underestimate IOP, particularly at high pressures, however the TONOVET Plus was highly correlated with manometric IOP in the clinically relevant range of 5–50 mmHg. The TONOVET Plus is an appropriate choice of instrument for measuring IOP in rabbit eyes in both research and clinical settings.